URGENSI PENDIDIKAN DALAM PERSPEKTIF ISLAM - Evi Nur Halimah (Qouman : Jurnal Pendidikan dan Studi Islam, 2025)
Thecondition of ignorance that dominated the Arab society in the pastwas tried to be changed by Islam. The Islamic education is oftencalled tarbiyah andta’lim al-tarbiyah which means education thatincludes aspects of science and morality. Therefore, Islamic educationis to cultivate humans’ minds andtoregulate humans’ charactersandattitudesbased on the Islamic teachings. Meanwhile al-ta’lim inIslamic education means teaching, which only gives knowledge to thestudents. According to Islamic teachings, humans have two potentials(evil and piety). The teachings of Islam acknowledge the differences ofpeople’s talents but the differences do not mean that they cannot beformed at all. In order to achieve the goals well, education needs to beadapted with the development of thestudents.